P639 Validation of the Quantum Blue® infliximab-level rapid test in clinical practice of patients with inflammatory bowel disease. (16th January 2018) - Strik, A; Schuster, T; Löwenberg, M; Ponsioen, C; D'Haens, G
Abstract: Background: Sub therapeutic serum drug levels of infliximab (IFX) are associated with poor clinical and endoscopic outcome in patients with inflammatory bowel disease (IBD). To make proactive dose adjustments to optimise IFX therapy, quick results of serum drug level measurements are essential. Since results of the conventional bridging enzyme-linked immunosorbent assay (ELISA) are usually only available after a number of days due to the time-consuming character of the test, shipment of samples to external laboratories and administrative hurdles, there is a need for rapid 'point-of-care' assays in treatment with monoclonal antibodies. Most evidence about the validation of the rapid test is derived from spiking experiments. This abstract presents the results of the validation of the Quantum Blue ® IFX rapid test in routine care of IBD patients by comparing it with two different validated ELISAs. Methods: Serum samples for IFX measurements were prospectively obtained from IBD patients on IFX maintenance treatment after obtaining written consent. Samples were measured with the Quantum Blue ® Infliximab rapid test (BÜHLMANN Laboratories, Schönenbuch, Switzerland), Sanquin ELISA (Sanquin laboratories, Amsterdam, the Netherlands) and RIDASCREEN ® IFX ELISA monitoring kit (R-Biopharm, Darmstadt, Germany). Trough levels were measured just before infusion and mid-infusion levels during outpatient clinic visits for routine consultations (Weeks 3–5). Results of the two ELISA methods were compared with results obtained with the Quantum Blue ® Infliximab rapid test. Results: Thirty samples of IBD patients on IFX maintenance treatment were prospectively collected. The majority of the samples were taken at trough (83%) and 5 at mid-infusion. Three out of five mid-infusion level measurements exceeded the upper limit of the rapid test (20 µg/ml) and were excluded from the correlation. When comparing the Quantum Blue ® Infliximab rapid test with the Sanquin ELISA and the RIDASCREEN ® IFX ELISA, a correlation coefficient of 0.876 and 0.867 was found, respectively. The intraclass correlation coefficient (ICC) of the Quantum Blue ® Infliximab rapid test vs. the Sanquin ELISA was 0.729 (95% CI −0.31 to 0.91). After comparison of the rapid test with the RIDASCREEN ® IFX ELISA, an ICC of 0.824 (95% CI 0.240–0.940) was found. Conclusions: The Quantum Blue ® Infliximab rapid test is a good alternative for the time-consuming conventional ELISA method for the measurement of IFX serum concentrations at trough in IBD patients receiving IFX maintenance treatment. This test can be used in routine care since results are available within 15 min which allows physicians to make proactive adjustments in dosing.